Fire ice : a novel from the NUMA files - Cussler, Clive (Cussler, Clive. NUMA files., 2002)
Kurt Austin is preparing for an interview while aboard a research vessel in the Black Sea. But his television spot suddenly becomes a rescue missionwhen the waiting film crew is attacked on a nearby island. With little information on the attackers, and no clue to their true agenda, Austin is forced to turn to an unlikely source: his old KGB Cold War adversary Vladimir Petrov. According to Petrov, the island is actually an old submarine base that<U+2019>s been commandeered by clever mobster-turned-billionaire-businessman Mikhail Razov. Razov is certain he descends from the great Romanov family and he<U+2019>s out to reclaim his rightful position as czar of Russia. With a powerful resource called “fire ice”, discovered by his mining company, Razov may just have the ammunition he needs to take over the modern world. To stop him, Austin will have to work with Petrov. And he<U+2019>ll have to find out fast how much trust he can offer an old nemesis in this thrilling adventure that “goes down like a chilled Stolichnaya martini.” (Kirkus Reviews)